Steroidal but not embryonic regulation of mucin 1 expression in bovine endometrium - Kaiyu KUBOTA; Masafumi MIWA; Ken-Go HAYASHI; Misa HOSOE; Miki SAKATANI (The Society for Reproduction and Development, 2021)
In cow herd management, inadequate embryo implantation leads to pregnancy loss and causes severe economic losses. Thus, it is crucial to understand the molecular mechanisms underlying endometrial receptivity and subsequent embryo implantation. Transmembrane glycocalyx mucin 1 (MUC1) has a large and highly glycosylated extracellular domain known to inhibit embryo implantation via steric hindrance. The role of MUC1 in the bovine endometrium remains to be explored. Herein, we used simple but reliable in vivo and in vitro experiments to investigate the expression and regulation of MUC1 in the bovine endometrium. MUC1 gene expression was analyzed in endometrial epithelial cells collected by the cytobrush technique using reverse transcription-quantitative polymerase chain reaction. MUC1 protein expression was evaluated by immunohistochemical analysis of endometrial samples collected from slaughtered cows. We used an in vitro cell culture model to study the regulation of MUC1 expression by treating cells with sex steroidal hormones or co-culturing cells with a blastocyst. The results revealed that MUC1 was expressed and localized to the apical surface of luminal epithelial cells in the bovine endometrium. MUC1 expression disappeared during the luteal phase of the estrous cycle and during pregnancy. 17β-estradiol induced MUC1 expression, whereas progesterone inhibited its increase and co-culturing with blastocysts did not affect the expression. A long postpartum interval is a known risk factor for reduced fertility, and MUC1 expression was higher in this compromised condition. Our results demonstrated the MUC1 regulation by steroid hormones in bovine endometrium for embryo implantation, and we observed a negative correlation between MUC1 expression and fertility.